INSTABILITY OF SOLITARY WAVE SOLUTIONS OF A CLASS OF NONLINEAR DISPERSIVE SYSTEMS - Hakkaev, Sevdzhan (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2004)
In this paper the orbital stability and instability properties of solitary wave solutions of a class of nonlinear dispersive systems are studied. By applying the abstract results of Grillakis et al. ([11]), we obtain the stability of the solitary waves.